2012
DOI: 10.1186/1472-6882-12-171
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of ethanolic extract from Myagropsis myagroides on murine macrophages and mouse ear edema

Abstract: BackgroundThis study aims to investigate anti-inflammatory effect of ethanolic extract of Myagropsis myagroides (EMM) in the lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages and the phorbol 12-myristate 13-acetate (PMA)-induced ear edema in mice, and to clarify its underlying molecular mechanisms.MethodsThe levels of nitric oxide (NO), prostaglandin E2 (PGE2), and pro-inflammatory cytokines were measured by Griess assay and enzyme linked immunosorbent assay. The expressions of inducible nitric oxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Also, fucoxanthin, isolated from Myagropsis myagroides and L. japonica , inhibited the production of inflammatory mediators and pro‐inflammatory cytokines in RAW 264.7 macrophage cells . Among phlorotannins isolated from M. myagroides , 6,6′‐bieckol and phlorofucofuroeckol B are the major anti‐inflammatory components in the ethanolic extract and ethyl acetate fraction, respectively . We found that the hexane fraction from M. myagroides ethanolic extract (MMH) showed the highest anti‐inflammatory activity among various solvent fractions of the ethanolic extract.…”
Section: Introductionmentioning
confidence: 98%
“…Also, fucoxanthin, isolated from Myagropsis myagroides and L. japonica , inhibited the production of inflammatory mediators and pro‐inflammatory cytokines in RAW 264.7 macrophage cells . Among phlorotannins isolated from M. myagroides , 6,6′‐bieckol and phlorofucofuroeckol B are the major anti‐inflammatory components in the ethanolic extract and ethyl acetate fraction, respectively . We found that the hexane fraction from M. myagroides ethanolic extract (MMH) showed the highest anti‐inflammatory activity among various solvent fractions of the ethanolic extract.…”
Section: Introductionmentioning
confidence: 98%
“…(Anacardiaceae) inhibited the ear edema induced by TPA by 21%, while the methyl gallate, one of the main compounds in MeOH extract, at an equivalent concentration, produced 63% of ear edema inhibition. Likewise, an ethanolic extract of Myagropsis myagroides (90 μ g/ear) markedly inhibited the phorbol myristate acetate- (PMA-) induced ear edema with 66.8% inhibition ( P < 0.05), one-third of 6,6′-bieckol activity which was tested at 30 μ g/ear [ 44 ]. In this investigation, although the OFI extract showed an adequate inhibitory effect on ear edema, it did not exceed the effects observed with isorhamnetin diglycosides IGR and IGP.…”
Section: Discussionmentioning
confidence: 99%
“…fucoxanthin, fucosterol, phlorotannin (Kim et al, 2010b;Kim et al, 2013a;Lee et al, 2013;Jung et al, 2014). (Joung et al, 2012a;Joung et al, 2012b;Gwon et al, 2013;Kim et al, 2013b), phlorotannin, sargachromenol sargaquinoic acid (Kang et al, 2013;Kim et al, 2014 , 20 µL 5% nonidet NP-40 5 .…”
Section: Nf-b Inhibitor Of Kappa B (I B)mentioning
confidence: 99%